FRI0042 Anti-Carbamylated Protein Antibodies in Unaffected First-Degree Relatives of Rheumatoid Arthritis Patients: Lack of Correlation with Anti-Cyclic Citrullinated Protein Antibodies and Rheumatoid Factor. (9th June 2015) - Bartosiewicz, I.S.; Alessandri, C.; Pendolino, M.; Mancini, R.; Colasanti, T.; Pecani, A.; Mastrangelo, A.; Sabatinelli, D.; Riccieri, V.; Conti, F.; Di Franco, M.; Valesini, G.; et al.
Abstract : Objectives: To investigate the prevalence of anti-carbamylated protein antibodies (anti-CarP) in the Healthy first-degree relatives (HFDRs) of patients with Rheumatoid Arthritis (RA). Methods: We enrolled 141 HFDRs of 63 patients with RA diagnosed accordingly to the 2010 ACR/EULAR criteria. Fifty-six normal healthy subjects (NHS), sex and age matched, served as controls. Anti-CarP IgG, anti-cyclic citrullinated peptide antibody (anti-CCP) IgG and rheumatoid factors (RF) isotypes (IgG, IgA, IgM) were assessed by solid-phase ELISA. Results: Anti-CarP were detectable in 13 HFDRs (9.2%), anti-CCP in 9 (6.3%), IgG-RF in 10 (7%), IgA-RF in 17 (12%), and IgM-RF in 13 (9.2%) HFDRs. Twenty-nine (46%) RA patients were positive for anti-CarP, 31 (49.2%) for anti-CCP, and 34 (53.9%) for RF. One NHS (1.7%) resulted positive for anti-CarP, none for anti-CCP and RF. Anti-CarP showed a significantly higher prevalence in HFDRs than in NHS (p<0.0001). A significant correlation between anti-CCP and RF were found among RA patients (p=0.0002), whereas no correlations were reported between autoantibodies tested in the HFDRs. Conclusions: Anti-CarP can be found in the sera of HFDRs of RA patients and their prevalence is significantly higher than in NHS. No correlation of anti-CarP with anti-CCP and RF antibodies in RA HFDRs was found. References: Van Veelen PA, et al.: Autoantibodies recognizing carbamylated proteins are present in sera of patients with rheumatoid arthritis and predict joint damage. Proc Natl Acad Sci U S 2011; 42: 17372-7. Shi J et al.: Anti-carbamylated protein antibodies are present in arthralgia patients and predict the development of rheumatoid arthritis. Arth Rheum 2013; 4: 911-5. Shi J et al.: Anti-carbamylated protein antibodies are present in arthralgia patients and predict the development of rheumatoid arthritis. Arth Rheum 2013; 4: 911-5. Acknowledgements: This work has been supported by Fondazione Umberto Di Mario ONLUS. We thank Giuliana Giuliani and Stefania Mieli for their technical support Disclosure of Interest: None declared